基于SSR分子标记的油棕遗传多样性 及群体遗传结构分析Analysis of genetic diversity and population genetic structure in oil palm based on SSR markers - 刘加能1,2，程秋如1,2，潘登浪1，李炜芳1，彭小芸1,2，周若茹1,2， 周丽霞3，曾宪海1,3，刘子凡1,2 LIU Jianeng1,2，CHENG Qiuru1,2，PAN Denglang1，LI Weifang1，PENG Xiaoyun1,2， ZHOU Ruoru1,2，ZHOU Lixia3，ZENG Xianhai1,3，LIU Zifan1,2 (Zhongguo youzhi)
旨在为挖掘油棕优异种质提供参考，筛选30对SSR引物对605份油棕种质资源的遗传多样性和群体遗传结构进行分析。结果显示：30对SSR引物在所有资源中观察等位基因数（Na）平均值为11.933，有效等位基因数（Ne）平均值为4.116，多态性信息含量（PIC）平均值为0.711，表明SSR引物多态性较高，且种质间遗传多样性丰富；Structure分析将605份油棕种质分为2个组群，与主坐标分析结果一致，其中组群1的遗传多样性较组群2高，组群2的自交程度较组群1明显；个体非加权配对法聚类分析将605份油棕种质划分为3个组群，两两种质间遗传距离介于0.4~0.8的占94%，说明该群体的遗传组成简单；分子方差分析表明个体内变异（85%）高于个体间变异（10%）和群体间变异（5%），与两组群间遗传分化系数（0.025）低和基因流（9.613）高的结果相一致。综上，参试油棕种质群体遗传结构简单，群体水平上遗传分化程度较低，个体水平上遗传变异丰富，亟需重视对变异优株选择创制。In order to provide reference for the exploration of excellent oil palm germplasm, 30 pairs of SSR primers were screened to detect and analyze the genetic diversity and population genetic structure of 605 oil palm germplasm resources.The results showed that the mean value of number of observed alleles (Na) was 11.933, the mean value of effective number of alleles (Ne) was 4.116, and the mean value of polymorphism information content (PIC) was 0.711 for the 30 pairs of SSR primers across all resources, indicating that SSR primers were highly polymorphic and rich in genetic diversity among germplasm. The 605 germplasms were divided into two groups by Structure analysis, which was consistent with the results of principal coordinate analysis.The genetic diversity was higher in cluster 1 than that in cluster 2, and the degree of self-fertilization was significantly higher in cluster 2 than that in cluster 1. The 605 germplasms were divided into three groups by UPGMA cluster analysis, and 94% of the genetic distance between the two germplasm ranged from 0.4 to 0.8, indicating that the genetic composition of the population was simple. The molecular variance analysis showed that the intra-individual variation(85%)was higher than the inter-individual variation (10%)and inter-population(5%),which was consistent with the results of low genetic differentiation coefficient (0.025) and high gene flow(9.613) between the two groups. In general, the genetic structure of the tested germplasm population in this study is simple, the degree of genetic differentiation at the population level is low, and the genetic variation at the individual level is rich, which is urgent to pay attention to the selection and creation of mutant superior plants.